The Influence Of Financial And Non-Financial Company Information On Firm Value - Gunawan, Raynaldi; Wulandari, Putu Prima (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This quantitative study aims to examine the influence of financial and non-financial information on firm value in retail trade sub-sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. Financial data were used to measure firm size through total assets, number of employees, and number of retail branches, while business growth was assessed by calculating the annual percentage of asset growth. The non-financial information used includes the percentage of institutional ownership and the proportion of independent commissioners. Firm value was measured using the Tobin's Q ratio. Using a purposive sampling technique, 11 out of 37 companies were selected as the sample, resulting in 55 observational data points over five years. Secondary data from annual reports were analyzed using panel data regression with EViews 12 Student Version. This study finds that business growth does not affect firm value, while firm size, independent commissioners, managerial ownership, and institutional ownership significantly influence firm value.